THE ROLE OF FINANCIAL POLICY IN ENSURING MACROECONOMIC STABILITY - Jabborova Dilafruz (Scholars Digest Publishing, 2024)
Macroeconomics is a social science. Therefore, the timing of economic events cannot be precisely determined; it is possible to observe the behavior of macroeconomic agents and make approximate forecasts accordingly. In the process of analysis, economic models make the study of the economy much easier and explain the reasons for the main economic changes. In this article, research is conducted on the role of financial policy in ensuring macroeconomic stability and ways to improve it.
Keywords: Macroeconomics, fiscal policy, monetary policy, stability, financial policy, economic growthsh.